Pattern‐reconfigurable dual‐band dipole antenna array with four switchable beams for full coverage in horizontal plane - Chang‐Wei Su; Huayan Jin; Chung‐Yi Li; Yi‐Jyun Liao; Kuo‐Sheng Chin (IET Microwaves, Antennas & Propagation, 2021)
Abstract In this study, we develop a pattern‐reconfigurable dual‐band 1 × 2 dipole antenna array for operation in 2.45‐ and 5.5‐GHz bands. Parasitic directors are added to the antenna to change the shape of the radiation pattern, and the length of parasitic directors are adjusted using diode switches; therefore, each band can switch four beams in 0° (front broadside), 90° (right endfire), 180° (back broadside), and 270° (left endfire) directions to achieve full coverage in the horizontal plane. For demonstration, one prototype of the proposed pattern‐reconfigurable dual‐band dipole antenna array was fabricated and measured. Measured results indicated that dual‐band operation was achieved with the maximum impedance bandwidths of 30.8% and 46% in 2.45‐ and 5.5‐GHz bands, respectively. Four switchable beams were obtained with a maximum gain of 5.3 dBi and a front‐to‐back ratio up to 17.3 dB.